Implicit Preferences Inferred from Choice - Tom Cunningham; Jonathan de Quidt (Center for Economic Studies and ifo Institute (CESifo), 2016)
A longstanding distinction in psychology is between implicit and explicit preferences. Implicit preferences are ordinarily measured by observing non-choice data, such as response time. In this paper we introduce a method for inferring implicit preferences directly from choices. The necessary assumption is that implicit preferences toward an attribute (e.g. gender, race, sugar) have a stronger effect when the attribute is mixed with others, and so the decision becomes less “revealing” about one's preferences. We discuss reasons why preferences would have this property, advantages and disadvantages of this method relative to other measures of implicit preferences, and application to measuring implicit preferences in racial discrimination, self-control, and framing effects.
Keywords: D03; D83; J71; 330; implicit discrimination; bias; judgement and decision making; choice-set effects